Application of an articulating spacer in two‐stage revision for severe infection after total knee arthroplasty - Qiu, Xu‐sheng (Orthop Surg, 2010)
Objective:  To investigate the efficiency and safety of articulating spacer for severe infection after total knee arthroplasty (TKA) in patients with medical comorbidities and local sinus tracts. Methods:  Between January 2002 and March 2008, ten consecutive patients with late stage infected TKA complicated by local sinus tracts and medical comorbidities, were treated in our hospital by delayed two‐stage reimplantation using articulating spacers. The modified Hospital for Special Surgery (HSS) knee scoring system was used to evaluate the results. Results:  One patient underwent knee fusion as the infection could not be controlled after first‐stage surgery. Infection was eradicated in the other nine patients. The mean follow‐up was 50 months (range, 24–90 months), no recurrent infection developing in these nine patients. The average modified HSS score was 48 points (range, 32–63) before the first‐stage surgery, 79 points (range, 62–91) at the end of the spacer period, and 89 points (range, 74–95) at the latest follow‐up, and the good to excellent rate was 0%, 80% and 100%, respectively. The average range of motion had improved to 8° to 93° at the end of the spacer period, and 3° to 110° at the last follow‐up, compared to 13° to 70° preoperatively. Conclusion:  Delayed two‐stage reimplantation using an articulating spacer is effective for treating infected TKA in patients with medical comorbidities or local sinuses.